Radar Meteor Detection: Concept, Data Acquisition and Online Triggering - Leite, Eric V. C.; Alves, Gustavo de O. e; Seixas, José M. de; Marroquim, Fernando; Vianna, Cristina S.; Takai, Helio (IntechOpen, 2011)
None